Case Study : Chan Rak Ter Sdn. Bhd / Muhammad Amirul Saiful Bahry - Saiful Bahry, Muhammad Amirul (2021)
In this document will show the case study about Chan Rak ter Sdn. Bhd is a company that sells Chan rak ter and Chanrakies branded water and cookies. Hq company is located in Shah alam and has many agents selling its products and it will be a product that is quite famous in 2020 and 2021. Based on what I can study, this business started when a lot of branded water was produced by well-known entrepreneurs and it became a phenomenon in doing business like this, but some were well accepted by the community in Malaysia, but some were the other way around, but for this Chab rak ter brand it can be accepted by the community in the sale of its product in malaysia even though it is a product based on a Thai recipe in producing it in terms of name we already know that it is related to Thailand. During the case study what i have learned is how this product can survive in the market and can be accepted by a community and so on. The product also has no exceptions in the target of its sale in the market because it is open to all sections of society. The sale of this product has been established throughout Malaysia because it has an agent who sells this product, it can be purchased at retail stores and so on. In addition, this business has also provided many job opportunities to the community to generate daily income by becoming an agent of Chan rak ter and Chanrakies. This case study provides a platform for the opposite entrepreneurs to develop their potential by adapting the entrepreneurial competencies which proven success supported the findings.